2018
DOI: 10.1007/s11906-018-0807-9
|View full text |Cite
|
Sign up to set email alerts
|

Sympathomimetic Toxidromes and Other Pharmacological Causes of Acute Hypertension

Abstract: We will discuss designer stimulants, alpha and baclofen agonist withdrawal, and the clinical entity known as posterior reversible encephalopathy syndrome (PRES). Additionally, we examine the controversial "unopposed alpha" phenomenon which may result from use of beta-adrenergic antagonist in the presence of stimulant toxicity. These topics encompass clinical situations and disease entities that are increasingly encountered and are often either unanticipated or under-recognized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 79 publications
0
15
0
1
Order By: Relevance
“…Furthermore, several groups have recently begun to question the entire hypothesis of the unopposed alpha effect, noting that it has been incorrectly applied to any sympathomimetic agent, despite limited evidence of its utility in cocaine-based intoxications where its occurrence is inconsistent, rare and unpredictable [ [146] , [147] , [148] , [149] ]. Others have indicated that the unopposed alpha effect may in fact be more myth than reality, noting the original hypothesis may have simply been a misinterpretation of a phenomenon seen with Starling’s law while noting the lack of consideration for factors other than vascular tone which control blood pressure [ 150 ].…”
Section: Management/treatment Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, several groups have recently begun to question the entire hypothesis of the unopposed alpha effect, noting that it has been incorrectly applied to any sympathomimetic agent, despite limited evidence of its utility in cocaine-based intoxications where its occurrence is inconsistent, rare and unpredictable [ [146] , [147] , [148] , [149] ]. Others have indicated that the unopposed alpha effect may in fact be more myth than reality, noting the original hypothesis may have simply been a misinterpretation of a phenomenon seen with Starling’s law while noting the lack of consideration for factors other than vascular tone which control blood pressure [ 150 ].…”
Section: Management/treatment Strategiesmentioning
confidence: 99%
“…Starling’s law indicates that a decrease in heart rate as a result of beta 1-adrenergic antagonism could increase end diastolic pressure and cardiac fiber length, causing an increase in ventricular contraction and blood pressure [ 149 , 150 ]. Authors have also pointed out the lack of the unopposed alpha effect phenomenon despite widespread use of beta adrenergic antagonists to treat various sympathomimetic intoxications, including cocaine [ [146] , [147] , [148] , [149] , [150] ]. Some have indicated that the unopposed alpha effect may simply be a result of the pharmacological effects seen with cocaine intoxication, while others have indicated that the potential unopposed alpha effect seen after propranolol administration in cocaine intoxication may not be a class effect but is unique to propranolol itself [ 148 , 149 ].…”
Section: Management/treatment Strategiesmentioning
confidence: 99%
“…In all, psychostimulants present with a characteristic sympathomimetic toxidrome with a combination of effects on the heart and cardiovascular system which can include hypertension, tachycardia, myocardial ischaemia and infarction, various arrhythmias, vasospasm, arterial dissections, cardiomyopathy, stroke and intracranial haemorrhage .…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Baclofen is a well-known and widely prescribed gamma-aminobutyric acid B agonist for the management of spasticity. Sudden termination of baclofen, especially in cases of intrathecal pump malfunction, has been reported and can lead to a dangerous and potentially lethal withdrawal syndrome accompanied by hypertension, tachycardia, rebound spasticity, myoclonus and dystonia among others 4. King et al , along with other sympathomimetic toxidromes and hyperadrenergic states, described the baclofen withdrawal syndrome (BWS) in details including an overview of possible therapeutic avenues 4.…”
Section: Introductionmentioning
confidence: 99%
“…Sudden termination of baclofen, especially in cases of intrathecal pump malfunction, has been reported and can lead to a dangerous and potentially lethal withdrawal syndrome accompanied by hypertension, tachycardia, rebound spasticity, myoclonus and dystonia among others 4. King et al , along with other sympathomimetic toxidromes and hyperadrenergic states, described the baclofen withdrawal syndrome (BWS) in details including an overview of possible therapeutic avenues 4. Although less frequently reported but potentially as severe, BWS has also been described secondary to abrupt oral discontinuation 5…”
Section: Introductionmentioning
confidence: 99%